Penentuan Beban Kerja Transporter pada Departemen Assembly & Decoration di PT. X - Andre Kawilarang (Jurnal Titra, 2017)
PT. X attempts to determine transporters’ workload with packing process outside production area. Packing process outside production area causes addition of transporter’s job description and packing process adjustment. Addition of transporter’s job description problem can be solved using DILO method and standardized production process in assembly & decoration department. The result of the DILO method shows AD2 transporters have BKI 71.73% (first shift) and 73.07% (second shift). This shows that AD2 transporters still has idle time, so it is not overload and they are able to run 95 minutes (22%) of additional work plan. The proposed work instructions are designed on X, Y and Z products. The packing trial is done for product A, B and C which have box capacity 210 pcs, 672 pcs and 825 pcs.